The Effect of Human Development Index (HDI) on Poverty and Crime in West Kalimantan, Indonesia - Jamaliah Jamaliah; Elyta Elyta (UIN Sunan Gunung Djati, 2022)
The strategic problem faced by West Kalimantan Province is the problem of the high poverty rate. Compared to other provinces in Indonesia, the poverty rate in West Kalimantan is still relatively high. The human development index (HDI) in West Kalimantan has indeed increased yearly, but this increase is followed by relatively high poverty and crime. Based on the background described, the main problem in this study is the influence of HDI on poverty and crime in West Kalimantan. This study uses quantitative and descriptive approach as the method with multiple linear and panel data regression analyses. The results of this study are poverty with HDI has a negative relationship. Weather crime shows a positive relationship with HDI. In other word, HDI has an acceptable influence on crime. Moreover, poverty has a negative relationship to crime, meaning that if poverty increases by 1 percent, crime will decrease. The result of this research can be a basis for general considerations in dealing with poverty and reducing the number of crimes by improving the population’s quality as indicated by the HDI. All stakeholders’ effort needed to strengthen human quality by implementing programs in tackling poverty. For further research, this study suggests using an approach to the real conditions of poverty.